Digitalization, Leverage, and Liquidity as Determinants of Return on Equity: Evidence from Technology Firms Listed on the Indonesia Stock Exchange - Andriani, Nini; Putri Utami, Ayu; Azis R, Abdul; Jusmawati; Jannah Alwi, Miftahul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of digitalization and financial ratios on the financial performance of technology firms listed on the Indonesia Stock Exchange during 2020–2024. Digitalization is proxied by intangible assets, while financial ratios include DAR, DER, Current Ratio, and Quick Ratio. Using a quantitative approach with panel data regression on 17 selected firms, the results show that digitalization, DAR, and Quick Ratio positively and significantly affect Return on Equity (ROE), while DER and Current Ratio have a significant negative effect. These findings imply that digital transformation and financial structure play crucial roles in enhancing firm profitability. Keywords: Digitalization; Financial Ratios; Leverage; Liquidity; Return on Equity; Technology Firms; Panel Data